Correlations of Post-stroke Depression with Inflammatory Response Factors - Yuyuan MU; Zhichao WANG; Jiexin ZHOU; Chenxi TAN; Hongjiao WANG (Tehran University of Medical Sciences, 2018)
Background: We aimed to investigate the correlations of the inflammatory response factors, interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), high-sensitivity C-reactive protein (CRP), with patients with post-stroke depression (PSD), so as to provide a basis for the treatment and prevention of PSD for patients. Methods: The clinical laboratory data of 60 patients with PSD in The Second Affiliated Hospital of Qiqihar Medical University, Qiqihar, China from July 2016 to July 2017 and those of another 60 stroke patients without PSD admitted in the same period were analyzed retrospectively. The expression levels of inflammatory response factors in the two groups of patients and in PSD patients with different levels of depression were compared and analyzed via statistical methods. Multiple Logistic regression analysis was used to determine whether inflammatory response factors were independent risk factors for PSD patients. Results: The expression levels of IL-6, TNF-α and CRP in patients with PSD were significantly increased compared with those in patients without PSD, and the differences were statistically significant (t=6.429, t=6.355, t=5.792, P<0.001). The levels of IL-6, TNF-α and CRP had statistically significant differences between any two groups of mild, moderate and severe PSD patients (P<0.05). Results of multiple Logistic regression analysis revealed that the odds ratio (OR) values of inflammatory factors (IL-6, TNF-α and CRP) were 1.160, 1.099 and 1.248, respectively, and the corresponding p values were 0.020, 0.039 and 0.007 in patients of observation group, indicating the above three inflammatory response factors were independent risk factors for PSD. Conclusion: The clinic control on the expression levels of inflammatory response factors (IL-6, TNF-α and CRP) are extremely important for the treatment and prevention of PSD.